Metaphorical Representation of the Migration Crisis as a Natural Phenomenon of the Water Element (Based on American Media Texts) - N. V. Stepanova (Дискурс)
Introduction. This article is devoted to the consideration of American media-political discourse in the context of the migration crisis and is a fragment of a large-scale study of migration, racist, media-political and crisis discourse, as well as the discourse of enmity. The relevance of the study of migration discourse is evident, as migration processes and, in particular, the migration crisis have a significant impact on modern society and raise a number of serious, sometimes unmanageable issues for politicians. The article provides an analysis of discursive strategies typical of migration discourse, including an evaluation information strategy and discrediting tactics, as well as the role of cognitive metaphor in their implementation. Consideration of the actualization of migration discourse strategies at the linguistic-cognitive level, in the context of the theory of conceptual integration, allows us to distinguish various ways of metaphorical understanding of migration and the migration crisis, which constitutes the novelty of this study.Methodology and data sources. The study was conducted using the American periodicals. Texts were selected by a continuous sampling method. The study was conducted in the context of a critical approach to the analysis of discourse at the linguistic and linguistic-cognitive levels. The linguistic plan of the discourse was considered through the study of communicative strategies and tactics involved in media texts, using methods of discursive analysis, and semantic-stylistic/lexico-semantic analysis at certain stages. The main method of studying the linguistic-cognitive plan of discourse was cognitive-discursive analysis of the conceptual metaphor within the framework of the blending theory.Results and discussion. In the American migration discourse, a persuasive strategy has become widespread, which is often implemented through the evaluation information strategy. One of the main means of implementing the evaluation information strategy is the mechanism of cognitive metaphor. The conceptual signs identified during the analysis of the metaphor as a natural phenomenon of the water element can be explained by the natural characteristics of water as liquid and correlate with the number of migrants: the heating of water to the boiling point correlates with the critical mass of the number of migrants, the sharp breakthrough of water through the dam is compared to an excessive increase in the number of migrants. Also, the identified conceptual signs are associated with the effect of the surprise of what is happening (an unexpected influx of migrants as a bursting of the dam), a gradual and inconspicuous development of events (undermining the foundations of society and oppressing migrants as a slow destruction of soil by groundwater).Conclusion. The migration crisis is one of the key social problems of modern American society. The research conducted within the framework of blending theory provides an opportunity to identify specific ways of metaphorizing the migration crisis and to analyze various implications and background knowledge that are actualized as two scenarios of the same metaphor are implemented and displayed in the emergent structure of the blend.